Distinctive soil archaeal communities in different variants of tropical equatorial forest - Kerfahi, Dorsaf; Tripathi, Binu M.; Ferry Slik, J. W.; Sukri, Rahayu S.; Jaafar, Salwana; Adams, Jonathan M. (Springer, 2017)
Little is known of how soil archaeal community composition and diversity differ between local variants of tropical rainforests. We hypothesized that (1) as with plants, animals, fungi, and bacteria, the soil archaeal community would differ between different variants of tropical forest; (2) that spatially rarer forest variants would have a less diverse archaeal community than common ones; (3) that a history of forest disturbance would decrease archaeal alpha- and beta-diversity; and (4) that archaeal distributions within the forest would be governed more by deterministic than stochastic factors. We sampled soil across several different forest types within Brunei, Northwest Borneo. Soil DNA was extracted, and the 16S rRNA gene of archaea was sequenced using Illumina MiSeq. We found that (1) as hypothesized, there are distinct archaeal communities for each forest type, and community composition significantly correlates with soil parameters including pH, organic matter, and available phosphorous. (2) As hypothesized, the “rare” white sand forest variants kerangas and inland heath had lower archaeal diversity. A nestedness analysis showed that archaeal community in inland heath and kerangas was mainly a less diverse subset of that in dipterocarp forests. However, primary dipterocarp forest had the lowest beta-diversity among the other tropical forest types. (3) Also, as predicted, forest disturbance resulted in lower archaeal alpha-diversity—but increased beta-diversity in contrast with our predictions. (4) Contrary to our predictions, the BetaNTI of the various primary forest types indicated community assembly was mainly stochastic. The possible effects of these habitat and disturbance-related effects on N cycling should be investigated.
Keywords: Archaeal composition; Archaeal diversity; Kerangas; Tropical forests; Inland heath forest; White sand forest